The internationalization of emerging stock markets - Peter K. Cornelius (Intereconomics, 1994)
Stock markets in developing countries today account for about 7 per cent of world equity market capitalization, and this share is rising rapidly. Foreign investors have in the past often faced restrictive barriers to access to these emerging markets. A growing number of developing countries have now started to dismantle these barriers, however, resulting in an increasing interest by international portfolio managers in these emerging stock markets.
Keywords: 330; Foreign Investment